PERAN DINAS TENAGA KERJA DALAM PERLINDUNGAN KESELAMATAN DAN KESEHATAN KERJA BERDASARKAN PERATURAN BUPATI MOJOKERTO NOMOR 63 TAHUN 2016 (STUDI PADA DINAS TENAGA KERJA KABUPATEN MOJOKERTO) - Riza Fefriadi; Hufron Hufron; Sri Setyadji (Jurnal Akrab Juara, 2019)
The background of this writing is the problem that arises because of the high level of work accidents and many industrial companies who are negligent because they do not meet the factors to protect workers in the protection of occupational safety and health. Based on this, it is necessary to know the extent of the role of the Mojokerto Regency Manpower Office in the protection of occupational safety and health based on article 13 paragraph 2 letter d of the Mojokerto Regent Regulation Number 63 Year 2016 by the Mojokerto Regency Manpower Office, where to answer the above problems, then using this type of research empirical juridical law. As well as using a qualitative approach and using descriptive analysis techniques. The results showed that the reporting and supervision process was still lacking, where the monitoring process was not according to schedule. To support the performance of labor inspectors so that they can run more effectively, the solution is to increase the number of supervisory employees.